Preparation, Characterization and Bioactivities of Strawberry Polysaccharides - Libo Wang; Yumeng Zhao; Junwen Liu; Ling Zhu; Yanhui Wei; Kun Cheng; Yaqin Xu (Foods)
The aim of this research was to characterize the structure, physicochemical properties and anti-complement activities of two strawberry fruit polysaccharides (DSFP-500 and DSFP-700) obtained by ultrasonic degradation. The molecular weight (Mw) of DSFP-500 was 809 kDa and the Mw of DSFP-700 was 791 kDa, obviously lower than the 9479 kDa weight of the native polysaccharide (PSP). DSFP-500 and DSFP-700 were both composed of the same monosaccharides (Man, Rha, Gal, Glc, Gal and Ara) but the molar ratios were different. The two degraded polysaccharides had good thermal stabilities, as well as good water holding capacity (WHC) and oil holding capacity (OHC). The WHCs of DSFP-500 and DSFP-700 were 5.53 ± 0.08 and 5.70 ± 0.03 g water/g, and the OHCs of DSFP-500 and DSFP-700 were 9.34 ± 0.15 and 9.28 ± 0.29 g oil/g. DSFP-500 and DSFP-700 showed strong free radical scavenging activities in vitro; the ABTS+• scavenging rates of DSFP-700 and DSFP-500 were 55.97 ± 0.68% and 52.06 ± 0.85% at 4.0 mg/mL, respectively. Moreover, DSFP-500 and DSFP-700 both had anti-complement activities through the classical pathway and the alternative pathway, though DSFP-700 was more effective than DSFP-500. These findings indicated the potentiality of the degraded polysaccharides from strawberry fruits in functional food and medicine development.